INFECTION PROCESS AND MYCOTOXIN PRODUCTION IN FUSARIUM CULMORUM-INFECTED MAIZE EARS - Oldenburg, Elisabeth; Ellner, Frank (Plant Breeding and Seed Science, 2011)
Red ear rot of maize is an important disease in Europe caused by toxigenic Fusarium species like F. graminearum and F. culmorum. To get detailed information about the pathogenesis of the disease and the Fusarium toxin production in infected ears a field study was conducted with maize which was artificially inoculated with F. culmorum at the stage of female flowering. Every fortnight after inoculation, maize ears of two varieties were harvested and analysed for the progress of visual signs of the disease and related Fusarium toxin contamination. During the last harvest in mid October, external infection symptoms showing some small pale or brown-marbled kernels with dark brown rachillae were only observed at the ear tip, whereas internal symptoms visible within the rachis were much more pronounced and showed greyish –brownish or pink discolouration of the pith. The symptoms observed in rachis and kernels corresponded with the toxin contamination showing considerably higher concentrations in the rachis compared to the kernels and a top-down gradient from high to low toxin levels within the ear. This suggests that F. culmorum first infects the rachis from the tip towards the bottom, as it subsequently does the kernels via the rachillae connected to the rachis. As infection symptoms and mycotoxin production were much more pronounced in the rachis than in the kernels, red ear rot evaluation should be improved by observing signs of the disease in both kernels and the rachis.